2017
DOI: 10.1245/s10434-017-6098-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Response to Preoperative Therapy as a Novel Prognosticator for Ampullary and Duodenal Adenocarcinoma

Abstract: Background: The prognostic impact of pathologic response to preoperative therapy in patients with duodenal adenocarcinoma (DA) and ampullary adenocarcinoma (AMPA) has not been established. Methods: A retrospective review of 266 patients who underwent curative resection for DA (n=97) or AMPA (n=169) during 1993–2015 was performed. For patients who underwent preoperative therapy, pathologic response was systematically evaluated and classified as major (0%−49% of viable residual tumor cells) or minor (≥50% of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
5
1
2
Order By: Relevance
“…The authors concluded that recurrence was common and that repeat liver resection after recurrence was feasible only in a small subset of patients with modest survival benefit [ 94 ]. In a different multi-institutional study of 356 patients with ICC, 214 (60%) had a recurrence after surgical resection; 37 (17%) of these patients underwent subsequent surgical treatment for the recurrence with an associated 5-year OS of 44% [ 95 ]. Single-center studies comparing patients who underwent resection for recurrence ICC versus best supportive care or other liver-directed therapies/chemotherapy have demonstrated improved OS for resection; however, these studies need to be interpreted carefully due to significant selection bias and confounding due to the retrospective study design [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Management Of Recurrent Iccmentioning
confidence: 99%
“…The authors concluded that recurrence was common and that repeat liver resection after recurrence was feasible only in a small subset of patients with modest survival benefit [ 94 ]. In a different multi-institutional study of 356 patients with ICC, 214 (60%) had a recurrence after surgical resection; 37 (17%) of these patients underwent subsequent surgical treatment for the recurrence with an associated 5-year OS of 44% [ 95 ]. Single-center studies comparing patients who underwent resection for recurrence ICC versus best supportive care or other liver-directed therapies/chemotherapy have demonstrated improved OS for resection; however, these studies need to be interpreted carefully due to significant selection bias and confounding due to the retrospective study design [ 96 , 97 , 98 , 99 , 100 ].…”
Section: Management Of Recurrent Iccmentioning
confidence: 99%
“…Our study findings are consistent to the results of prior studies, and raise the question of what the role of neoadjuvant therapy should be in the treatment of DA. 9,12,18 Through a review of the NCDB and propensity score matching, our study has shown no statistically significant difference exists between the 30-day and 90-day mortality of patients receiving neoadjuvant therapy compared to adjuvant therapy. Furthermore, there was no statistically significant difference existing between the 2 cohorts for the overall survival at 1 year, 3 years, and 5 years.…”
Section: Discussionmentioning
confidence: 75%
“…11 Additionally, studies examining the pathological response of DA to neoadjuvant therapy have shown increased survival in carcinomas that responded well to therapy. 12 Further, evidence supporting the role of neoadjuvant therapy for DA has been shown in the effectiveness of this modality to facilitate "downstaging" in previously unresectable carcinomas. 9 Ecker et al evaluated the effect of adjuvant chemotherapy in small bowel adenocarcinoma on overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Однако исследование было некорректным, так как сравниваемые подгруппы отличались по тяжести сопутствующей патологии, размеру опухоли, морфологии и гистологическим подтипам [59]. S. Yamashita et al после морфологического анализа удаленных препаратов (после ПДР) у 79 пациентов с раком БСДК с предоперационным лечением пришли к заключению, что морфологический ответ (степень лечебного пато-морфоза) на неоадъювантную терапию может быть новым предиктором прогноза [60].…”
unclassified
“…Cloyd et al сообщили, что неоадъювантная терапия не увеличила частоту послеоперационных осложнений и реадмиссии, летальность [59]. По данным S. Yamashita et al, на этапе проведения неоадъювантной терапии из исследования выбыло 11 пациентов в связи с тяжестью состояния и прогрессией опухоли [60]. По нашим данным, осложнения при химиоэмболизации желудочно-двенадцатиперстнокишечной артерии наблюдались в 21,4 % случаев, лучевые реакции при дистанционной ЛТ -в 25 % наблюдений.…”
unclassified